Easy-To-Access Quinolone Derivatives Exhibiting Antibacterial and Anti-Parasitic Activities - Beteck, Richard M. (Molecules, 2021)
The cell wall of Mycobacterium tuberculosis (Mtb) has a unique structural organisation, comprising a high lipid content mixed with polysaccharides. This makes cell wall a formidable barrier impermeable to hydrophilic agents. In addition, during host infection, Mtb resides in macrophages within avascular necrotic granulomas and cavities, which shield the bacterium from the action of most antibiotics. To overcome these protective barriers, a new class of anti-TB agents exhibiting lipophilic character have been recommended by various reports in literature. Herein, a series of lipophilic heterocyclic quinolone compounds was synthesised and evaluated in vitro against pMSp12::GFP strain of Mtb, two protozoan parasites (Plasmodium falciparum and Trypanosoma brucei brucei) and against ESKAPE pathogens. The resultant compounds exhibited varied anti-Mtb activity with MIC(90) values in the range of 0.24–31 µM. Cross-screening against P. falciparum and T.b. brucei, identified several compounds with antiprotozoal activities in the range of 0.4–20 µM. Compounds were generally inactive against ESKAPE pathogens, with only compounds 8c, 8g and 13 exhibiting moderate to poor activity against S. aureus and A. baumannii.